Hamlet : a critical reader - Taylor, Neil, 1943- (Arden early modern drama., 2016)
Arden Early Modern Drama Guides offer students and academics practical and accessible introductions to the critical and performance contexts of key Elizabethan and Jacobean plays. Essays from leading international scholars give invaluable insight into the text by presenting a range of critical perspectives, making the books ideal companions for study and research. Key Features include: Essays on the play's critical and performance history, A keynote essay on current research and thinking about the play, A selection of new essays by leading scholars, A survey of resources to direct students' further reading about the play in print and online. To explore the critical and performance history of Hamlet is to engage with some of the most important moments in the intellectual, political and religious life of Europe, the English-speaking world and beyond over the last 400 years. From its complicated textual origins and its uneasy reputation for eccentricity in the eighteenth century, Hamlet has become a formidable global phenomenon, performed, read, studied, rewritten, adapted, illustrated and filmed more than any other of Shakespeare's plays. The essay in this volume help readers to understand how this phenomenon has developed and how it is still developing: what does Hamlet mean, and what does it mean to us?